2010
DOI: 10.1371/journal.pone.0009764
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Plasticity in the Hippocampus of a APP/PS1 Mouse Model of Alzheimer's Disease Is Impaired in Old but Not Young Mice

Abstract: BackgroundAlzheimer disease (AD) is a neurodegenerative disorder for which there is no cure. We have investigated synaptic plasticity in area CA1 in a novel AD mouse model (APPPS1-21) which expresses the Swedish mutation of APP and the L166P mutation of human PS-1. This model shows initial plaque formation at 2 months in the neocortex and 4 months in the hippocampus and displays β−amyloid-associated pathologies and learning impairments.Methodology/Principal FindingsWe tested long-term potentiation (LTP) and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
110
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 30 publications
17
110
3
Order By: Relevance
“…In our study, first, we demonstrated that excess formaldehyde suppresses hippocampal LTP and spatial memory formation in rats (Figs. 2 and 4), consistent with other reports of hippocampal LTP suppression and memory decline in aged mice and rats (Almaguer et al 2002;Chapman et al 1999;Kamal et al 2005), STZ-induced diabetic SD rats (Reisi et al 2010), and Alzheimer's disease animal models such as APP transgenic mice (Gureviciene et al 2004), APP/ PS1 mice (Gengler et al 2010), and SAMP8 (López-Ramos et al 2012). Second, we showed that excess formaldehyde non-specifically blocks the NR1/NR2B subunits of the NMDA receptor in vitro (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, first, we demonstrated that excess formaldehyde suppresses hippocampal LTP and spatial memory formation in rats (Figs. 2 and 4), consistent with other reports of hippocampal LTP suppression and memory decline in aged mice and rats (Almaguer et al 2002;Chapman et al 1999;Kamal et al 2005), STZ-induced diabetic SD rats (Reisi et al 2010), and Alzheimer's disease animal models such as APP transgenic mice (Gureviciene et al 2004), APP/ PS1 mice (Gengler et al 2010), and SAMP8 (López-Ramos et al 2012). Second, we showed that excess formaldehyde non-specifically blocks the NR1/NR2B subunits of the NMDA receptor in vitro (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Abundant evidence shows that memory decline occurs and hippocampal long-term potentiation (LTP) is impaired in aged animals (Almaguer et al 2002;Chapman et al 1999;Kamal et al 2005) and memory-deteriorating animal models such as amyloid precursor protein (APP) transgenic mice (Gureviciene et al 2004), APP/PS1 mice (Gengler et al 2010), and senescence-acceleratedprone 8 mice (SAMP8) (López-Ramos et al 2012). NR2B, one of the subunits of N-methyl-D-aspartate (NMDA) receptor, is critical in regulating the agedependent synaptic plasticity and memory formation (Tang et al 1999).…”
mentioning
confidence: 99%
“…Spatial learning deficits in the Morris water-maze, Y-maze, and contextual fear task had been reported in APPPS1 mice. 12,15 These deficits were detected in 8-month-old but not in younger APPPS1 mice. The episodic memory impairment is a cardinal symptom of AD and precedes a more global cognitive impairment.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have shown that the GLP-1 and GLP-1 analogs such as Val(8)GLP-1 cross the BBB (Kastin et al, 2002;Gengler et al, 2010b). Peripheral injection of GLP-1 analogs intraperitoneally increased neuronal progenitor proliferation in the brain (During et al, 2003) and enhanced LTP and paired-pulse facilitation (PPF) in the hippocampus (Gengler et al, 2010a). These results suggest that treatment with GLP-1 analogs beneficially affects a number of the therapeutic targets associated with AD, such as impaired cognitive performance, reduced neuronal communication, neurodegenerative processes, and reduced neuronal regeneration (Hölscher and Li, 2010).…”
Section: Introductionmentioning
confidence: 99%